Reliable Intelligent Path Following Control for a Robotic Airship Against Sensor Faults - Wang, Yueying; Zhou, Weixiang; Luo, Jun; Yan, Huaicheng; Pu, Huayan; Peng, Yan (IEEE/ASME transactions on mechatronics, 2019)
This paper presents a reliable intelligent path following control method for a robotic airship subject to sensor faults. First, an adaptive backstepping sliding mode controller is designed based on the six degrees of freedom model of airship, where the backstepping technique is used to obtain the desired velocities, and the adaptive sliding mode method is adopted to deal with the unknown model uncertainties. The stabilization of the whole path following control system is studied based on Lyapunov stability theory. Specially, since the measured data in the airship control system are interrelated, a data-driven soft sensor based on adaptive neuro-fuzzy inference system is designed to detect and isolate the sensor fault. Based on the developed detection and isolation mechanism, the airship control system still work well in the presence of sensor fault. Finally, simulations are given to demonstrate the effectiveness of the proposed path following strategy.